1974
DOI: 10.1073/pnas.71.12.4915
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Meromyosin Mg-ATPase: Presteady-State and Steady-State H + Release

Abstract: The presteady state and steady state release of protons during hydrolysis of ATP by myosin has been studied by using a proteolytic subfragment of myosin, heavy meromyosin, isolated from rabbit skeletal muscle. Under the conditions of 0.5 M KCI, 9 mM MgCI2, pH 8, and 250, the rate of the H+ initial burst is proportional to the concentration of ATP added, and shows no plateau even when the concentration of ATP added is increased up to 750 ,AM. The apparent second order rate constant is approximately 7 X 105 M-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In the second case, it has been shown that a transient proton release associated with the isomerization of heavy meromyosin occurs in the first steps of the hydrolysis at 20 °C (Koretz & Taylor, 1975;Chock & Eisenberg, 1974). This proton burst (-0.6 mol of H+/mol of enzyme at pH 8) is also observed at 20 °C or even at -7.5 °C, as shown in the present work, following the binding of various ATP analogues or ADP (Marsh et al, 1977) to the enzyme.…”
Section: Discussionsupporting
confidence: 79%
“…In the second case, it has been shown that a transient proton release associated with the isomerization of heavy meromyosin occurs in the first steps of the hydrolysis at 20 °C (Koretz & Taylor, 1975;Chock & Eisenberg, 1974). This proton burst (-0.6 mol of H+/mol of enzyme at pH 8) is also observed at 20 °C or even at -7.5 °C, as shown in the present work, following the binding of various ATP analogues or ADP (Marsh et al, 1977) to the enzyme.…”
Section: Discussionsupporting
confidence: 79%
“…The largest proton release would be observed at lower pHs, where the residue is largely protonated prior to reaction. Proton release accompanying the transient fluorescence enhancement has been measured for skeletal SI (Finlayson & Taylor, 1969;Chock & Eisenberg, 1974;Korentz & Taylor, 1975;Marsh et al, 1977;Chock, 1981), and the extent of proton release does decrease with increasing pH (Marsh et al, 1977). However, whether proton release occurs upon isomerization or cleavage has been a point of controversy.…”
Section: Discussionmentioning
confidence: 99%
“…Stopped-Flow Apparatus. The stopped-flow apparatus used here essentially consists of a mercury-xenon arc light source powered with a Kepco JQE power supply, a Bausch and Lomb grating monochromator equipped with a manual lens shutter and adjustable slits, a thermostated two-syringe Aminco-Morrow stopped-flow pneumatic drive system equipped with a modified mixer flow cell (Chock and Eisenberg, 1974) the temperature of which was directly read via a Teflon probe attached to the outer wall of the observation flow cell and registered on a Yellow Spring Instrument tele-thermometer, an EMI 9558 QBS-20 photomultiplier tube powered by a Keithley 245 high-voltage supply, a fast interacting signal amplifying system (Rhee and Chock, 1976), and a Tektronix WP-1200 digital processing system where waveform averagings and computations were carried out.…”
Section: Methodsmentioning
confidence: 99%